Horizontal bands and perforated stone screens - 008 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ The horizontal bands of elephants, horses, creepers are a common feature across all Hoysala temples. The perforacted stone screens can also be seen in most of the Hoysala era temples.